The Degree Of Employment Of The International Standard (ISO 21001: 2018) In The Management Of Syrian Educational Institutions, And The Requirements For its Application (Case Study: Workers In The Syrian Central Educational Administration) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of the research is to identify the degree of employing the international standard (ISO 21001: 2018) in the management of Syrian educational institutions, and the requirements for its application, in the Syrian central educational administration, and the research community consisted of employees working in the central educational administration building in the Syrian Arab Republic, whose number is according to statistics The Ministry of Education for the year 2021 has (700) male and female employees, (285) males and (415) females. The researcher used a questionnaire consisting of (30) paragraphs as a research tool. The researcher followed the analytical descriptive approach to achieve the research objectives. The research sample consisted of (70) male and female employees, and the research was conducted in the last quarter of 2022, and the most important results were the following:     1-  The degree of employing the international standard (ISO 21001: 2018)) in the Syrian central educational administration, according to the opinions of the respondents, was low in most of the questionnaire items.                                                                                                  2- The degree of requirements for the application of the international standard (ISO 21001: 2018) was (3.05), and this indicates that the respondents agreed, to a moderate degree, with most of the questionnaire items related to the requirements for the application of the standard in the Syrian central educational administration.                                                                         3- There are statistically significant differences attributed to the variables of academic qualification, administrative level, and number of training courses, on the degree of estimation of the requirements of applying the international standard (ISO 21001:2018).
Keywords: International Standard (ISO 21001:2018); management of educational institutions